A study of surgical site infections in a general practice hospital - Ravi Kumar, Thota Venkata; Goud, K. Anand (International Surgery Journal, 2019)
Background: Surgical site infections (SSI), major contributor to increased morbidity, mortality and healthcare costs among surgical patients worldwide. This study evaluates the incidence of surgical site infections in abdominal surgeries. Methods: This prospective observational study was conducted at Siri hospital, Khammam after obtaining permission from the hospital ethics committee. A total of 250 patients of elective and emergency abdominal surgery were included and studied about surgical site infections and factors influencing it. Results: This study includes 250 patients with abdominal abnormalities. In this 48(19.2%) patients were recorded with surgical site infection. As the age increases SSI was also increases. ASA scores of III (5.6%) & IV (8.0%) were associated with the increased SSI. These SSI were more common in intestinal obstruction with gangrene cases 7 (2.8%) and also in accidental trauma/injury cases 7 (2.8%). SSI can be noticed after 48 hour of infection and recorded up to 10 days of postoperative period. The surgical wound incidence was clean (14.6%), clean contaminated (29.2%), contaminated (20.8%) and dirty (35.4%) respectively. Major factors that influence the SSI were diabetes, obesity, pre-operative anti biotic usage, duration of surgery, emergency surgery and level of haemoglobin and albumin levels. The organisms isolated from SSI were E.coli (22.9%), Methicillin Resistant Staphylococcus aureus (18.7%), Proteus species (16.6%), Klebsiella species (16.6%), Pseudomonas aeruginosa (8.3%), Staphylococcus aureus (6.2%) and mixed bacterial infections (10.4%). Conclusions: Surgical site infections were more commonly seen in abdominal surgeries. SSI was higher in older people. Control of factors influencing and bacterial contamination decreases the incidence of SSI in abdominal surgeries.